Materiais de mudança de fase (PCM) no condicionamento passivo de habitações no semiárido brasileiro - Sousa, Diego Aristófanes Dias de (2020)
This work aims to study external walls of naturally conditioned houses in the context of the Brazilian Semiarid. It specifically focuses on the promotion of thermal inertia by applying materials with large latent heat energy storage capacity, the Phase Change Materials – PCM. The research has an exploratory nature and a quantitative approach, with literature review, computer simulation and data collection and systematic analysis as methodological procedures. It relies on whole-building thermal energy simulation software (specifically EnergyPlus 9.2) and weather data files, as well as statistical tools for data analysis and visual algorithmic programming platforms for the automation of computational processes (Grashopper + Ladtbug + Honeybee). The simulations take into account a computational model of a room in a multifamily housing of social interest, simulating specific material properties, internal loads and window opening routine. The thermal properties of the Octadecane (C18H38) were used as reference for the PCM simulations, considering its phase change hysteresis. From the model of the referred room and weather files of Brazilian Semiarid municipalities, energy flow and surface temperature data of the external walls were obtained, as well as the estimation of the annual Comfort Percentage (adaptive model). In the analysis, for each municipality, three factors were taken into account regarding the implementation of the PCM into the walls: orientation (position according to external or internal faces); PCM layer thickness (5 to 20 mm range, with 5 mm interval); and melting temperature (19 to 31 °C range, with 2 °C interval). The results of the simulations for each combination of factors were compared to the result of a room without PCM. Under the studied circumstances, the results showed that: external walls with PCM on exterior surfaces present greater Thermal Inertia, with effective reduction of heat gains; the walls with 20mm PCM layer showed greater Thermal Inertia; greater Thermal Inertia on walls does not imply increment of environmental comfort, being estimated that near 23% of the municipalities in the Brazilian Semiarid region is not benefited from the use of PCMs; and that the Annual Average Temperature is a more determinant climatic factor than the Average Daily Amplitude in the prediction of the contribution of PCMs to increase the comfort. Despite not presenting optimistic results regarding the use of PCMs in the studied context, this work contributes to the expansion of the scope of studies on the application of PCMs in tropical contexts, taking into account a naturally ventilated environment and embracing the reality of Brazilian social housing. Finally, the study is an addition to the hitherto reduced number of studies that simulate the effects of PCM hysteresis on building's thermal performance with EnergyPlus.